Effects Of Heat Moisture Treatment On The Physicochemical Properties Of Legume Flours - Abdul Wahid, Nur Hafizah (Pusat Pengajian Teknologi Industri, 2021)
Heat moisture treatment (HMT) is a hydrothermal treatment that changes the physicochemical properties of resistant starch by facilitating starch interaction within the amorphous and crystalline regions and/or disrupting starch crystals. In this study, HMT was used to modify legume flours (mung bean and chickpea flour) and physicochemical properties and resistant starch content were analyzed. The starches have been treated at 30% moisture content for 16 h at 100 °C. From the results, heat moisture treatment of mung bean flour (HMB) and heat moisture treatment of chickpea flour (HCP) show a significant decrease (p<0.05) in amylose content, due to heat induce by HMT, that able to change the amylose conformation, reduce the ability of amylose to form a complex with iodine.